Respuesta :
we are given
[tex]10x^2-y=48[/tex]
[tex]2y=16x^2+48[/tex]
Firstly, we will solve for y
[tex]y=8x^2+24[/tex]
now, we can plug that into first equation
[tex]10x^2-(8x^2+24)=48[/tex]
now, we can simplify it
[tex]10x^2-8x^2-24=48[/tex]
[tex]2x^2-24=48[/tex]
Add both sides by 24
[tex]2x^2-24+24=48+24[/tex]
[tex]2x^2=48+24[/tex]
[tex]2x^2=72[/tex]
Divide both sides by 2
[tex]x^2=36[/tex]
now, we can solve for x
[tex]x=-6,x=6[/tex]
now, we can find y-value
[tex]y=8x^2+24[/tex]
At x=-6:
we can plug x=-6
[tex]y=8(-6)^2+24[/tex]
[tex]y=8\times 36+24[/tex]
[tex]y=312[/tex]
At x=6:
we can plug x=6
[tex]y=8(6)^2+24[/tex]
[tex]y=8\times 36+24[/tex]
[tex]y=312[/tex]
so, we get solution as
C) (6, 312) and (-6, 312)..........Answer